2009
DOI: 10.1039/b811942b
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of humic acids in surface water: effects of divalent cations, pH, and filtration

Abstract: Humic acids (HAs) content of raw water is an important analytical parameter in water treatment facilities because HAs in the presence of chlorine may lead to the formation of dangerous by-products (e.g., trihalomethanes). The concentration of HAs in water is not directly accessible by common analytical methods due to their heterogeneous chemical structure. The aim of this study was to compare two methods to assess humic acids (HAs) in surface water namely absorbance of ultraviolet light at 254 nm (UV(254)) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 42 publications
5
67
0
4
Order By: Relevance
“…They also found that the size of the earlier-eluting peak was reduced by prior treatment with the hydrophobic resin XAD-16. This was attributed to the presence of humic substances, which are known to absorb strongly at 254 nm (Rodrigues et al, 2009). The relative retention times of the peaks detected at 254 and 280 nm in our CSW and OSW samples appear to be consistent with these findings.…”
Section: Discussionsupporting
confidence: 79%
“…They also found that the size of the earlier-eluting peak was reduced by prior treatment with the hydrophobic resin XAD-16. This was attributed to the presence of humic substances, which are known to absorb strongly at 254 nm (Rodrigues et al, 2009). The relative retention times of the peaks detected at 254 and 280 nm in our CSW and OSW samples appear to be consistent with these findings.…”
Section: Discussionsupporting
confidence: 79%
“…53680) and superoxide dismutase (SOD, 99%) were purchased from Sigma Aldrich, Inc., Milwaukee, WI. The elemental composition of the HA has been reported to contain: 48.36% of C, 26.91% of O, 4.24%of H, 0.78% of N, and 0.78% of S, and its atomic ratios (1.04 (H/C), 0.42 (O/C), and 0.012 (N/C)) reported in the literature are within the values for soil HAs, except for the N/C ratio [25]. High-performance liquid chromatography (HPLC) grade acetonitrile was acquired from Tedia Inc., Fairfield, OH.…”
Section: Chemicalssupporting
confidence: 75%
“…Soluble e-caprolactone was measured by high performance liquid chromatography (HPLC, Knauer) with a UV-vis detector. Total organic carbon (TOC) was determined by the combustion-infrared method (Rodrigues et al 2009) using a Shimadzu TOC-5000A analyzer (Labonal, Portugal). The biofilm formed on PCL carriers was quantified according to Rodrigues et al (2010) in the end of the experiments.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Physical and chemical processes such as reverse osmosis, ion exchange and electrodialysis are considered the best available technologies (BAT) to treat nitrate-contaminated water (Haugen et al 2002). In spite of the high efficiency to remove nitrate, BATs are expensive and present an elevated technological complexity (Della Rocca et al 2007) compared to biological nitrate removal (Robertson et al 2000;Su and Puls 2006;). Nitrate can be reduced mainly to dinitrogen gas by the activity of heterotrophic bacteria using organic carbon as the source of electrons (Rivett et al 2008).…”
Section: Introductionmentioning
confidence: 99%